Analisis Kemampuan Komunikasi Matematis Siswa SMP dalam Menyelesaikan Soal Aljabar Ditinjau dari Gaya Belajar - Maiyada, Annisa; Abadi, Agung Prasetyo (Polinomial : Jurnal Pendidikan Matematika, 2025)
Awareness of the importance of paying attention to learning styles in improving students' mathematical communication skills forms the background to this study. Because each student has a unique learning style, this affects the way they think, understand, and communicate mathematical concepts, especially in algebra. The purpose of this study was to analyze the mathematical communication skills of eighth-grade junior high school students in algebra material as viewed from the VARK learning styles (visual, auditory, read/write, and kinesthetic). The method used was qualitative research with a descriptive approach. This study involved 36 eighth-grade students at a public junior high school in Karawang, which was conducted over two days in the middle of the even semester of the 2024/2025 academic year. The research subjects were selected based on the dominance of one learning style type, with each type represented by one student who had the highest score and good communication skills. The research instruments consisted of three essay questions to measure mathematical communication skills, a learning style questionnaire, and interview guidelines. The results showed that students' mathematical communication skills based on the VARK learning style were generally classified as very good, with an overall average score of 93.7 and success in completing all the indicators tested. Each learning style had its own characteristics. Overall, this study indicated that a learning approach tailored to students' learning styles could improve their mathematical communication skills.